Energy Depletion of Bovine Mammary Epithelial Cells Activates AMPK and Suppresses Protein Synthesis Through Inhibition of mTORC1 Signaling - Burgos, S. A.; Kim, J.J. M.; Dai, M.; Cant, J. P. (Hormone and Metabolic Research, 2013)
The molecular mechanisms by which cellular energy status regulates global protein synthesis in mammary epithelial cells have not been characterized. The objective of this study was to examine the effect of AMP-activated protein kinase (AMPK) activation by 2-deoxyglucose on protein synthesis and the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway in bovine mammary epithelial cells. Phosphorylation of AMPK at Thr172 increased by 1.4-fold within 5 min, and remained elevated throughout a 30-min time course, in response to 2-deoxyglucose. Global rates of protein synthesis declined by 78% of control values. The decline in protein synthesis was associated with repression of mTORC1 signaling, as indicated by reduced phosphorylation of ribosomal protein S6 kinase 1 and eIF4E binding protein-1 (4E-BP1). Phosphorylation of ER-stress marker eIF2α was also increased but only at 30 min of 2-deoxyglucose exposure. 2-Deoxyglucose increased phosphorylation of tuberous sclerosis complex 2 (TSC2) on AMPK consensus sites but did not change the amount of TSC1 bound to TSC2. Activation of AMPK did not result in changes in the amount of raptor bound to mTOR. The inhibitory effects of AMPK activation on mTORC1 signaling were associated with a marked increase in Ser792 phosphorylation on raptor. Collectively, the results suggest that activation of AMPK represses global protein synthesis in mammary epithelial cells through inhibition of mTORC1 signaling.
Keywords: 2-deoxyglucose; mTOR; tuberous sclerosis complex; eIF2